Role of turbulence and electric fields in the formation of transport barriers and the establishment of improved confinement in tokamak plasmas through inter-machine comparison - Van Oost, G.; Bulanin, V.; Donné, A.J.H.; Gusakov, E.; Krämer-Flecken, A.; Krupnik, L.; Heikkinen, J.; Melnikov, A.; Razumova, K.; Rozhansky, V.; Stöcke, J.; Tendler, M.; et al. (Вопросы атомной науки и техники, 2009)
Over the past decade new regimes of tokamak operation have been identified, whereby electrostatic and magnetic turbulence
responsible for anomalous transport, can be externally suppressed, leading to improved confinement. Although turbulence
measurements have been performed on many confinement devices, the insight gained from these experiments is relatively
limited. To make further progress in the understanding of plasma turbulence in relation to improved confinement and transport
barriers, an extensive experimental and theoretical research programme should be undertaken. The present INTAS project
investigates the correlations between on the one hand the occurrence of transport barriers and improved confinement in the
tokamaks TEXTOR & T-10 and Tore Supra as well as on the smaller-scale tokamaks FT-2, TUMAN-3M and CASTOR, and on
the other hand electric fields, modified magnetic shear and electrostatic and magnetic turbulence using advanced diagnostics with
high spatial and temporal resolution. This is done in a strongly coordinated way and exploiting the complementarity of TEXTOR
and T-10 and the backup potential of the other tokamaks, which together have all the relevant experimental tools and theoretical
expertise. Advanced theoretical models and numerical simulations are used to check the experimental results. За останні десять років було отримано нові режими роботи токамаків, у яких електростатична і магнітна
турбулентність, відповідальна за аномальний перенос, могла заглушатися шляхом зовнішнього впливу, і тим самим
досягалося поліпшене утримання. Незважаючи на те, що дослідження турбулентності проводилися на багатьох установках,
розуміння цих процесів залишається досить обмеженим. Для досягнення подальшого прогресу в розумінні плазмової
турбулентності з погляду поліпшеного утримання і транспортних бар'єрів необхідні інтенсивні експериментальні і
теоретичні дослідження. Проект INTAS спрямовано на з'ясування кореляції між виникненням транспортних бар'єрів і
поліпшеного утримання в токамаках TEXTOR, Т-10 і Tore Supra, а також у токамаках малих розмірів ФТ-2, ТУМАН-3М и
CASTOR, з одного боку, і електричними полями, модифікованим магнітним широм і електростатичною і магнітною
турбулентністю, з іншого боку, з використанням передових діагностичних засобів з високим просторовим і тимчасовим
розділенням. Дослідження проводяться з високим ступенем координації робіт і використанням взаємодоповнюваності
установок TEXTOR і Т-10, і можливостей інших токамаків, що в сукупності забезпечить необхідну експериментальну і
теоретичну перевірку. Для перевірки експериментальних результатів буде використано нові теоретичні моделі і чисельне
моделювання. В последние десять лет были получены новые режимы работы токамаков, в которых электростатическая и магнитная
турбулентность, ответственная за аномальный перенос, могла подавляться путём внешнего воздействия, и тем самым
достигалось улучшенное удержание. Несмотря на то, что исследования турбулентности проводились на многих установках,
понимание этих процессов остаётся весьма ограниченным. Для достижения дальнейшего прогресса в понимании
плазменной турбулентности с точки зрения улучшенного удержания и транспортных барьеров необходимы интенсивные
экспериментальные и теоретические исследования. Проект INTAS направлен на выяснение корреляции между
возникновением транспортных барьеров и улучшенного удержания в токамаках TEXTOR, Т-10 и Tore Supra, а также в
токамаках малых размеров ФТ-2, ТУМАН-3М и CASTOR, с одной стороны, и электрическими полями, модифицированным
магнитным широм и электростатической и магнитной турбулентностью, с другой стороны, с использованием передовых
диагностических средств с высоким пространственным и временным разрешением. Исследования проводятся с высокой
степенью координации работ и использованием взаимодополняемости установок TEXTOR и Т-10, и возможностей других
токамаков, что в совокупности обеспечит необходимую экспериментальную и теоретическую проверку. Для проверки
экспериментальных результатов будут использованы новые теоретические модели и численное моделирование.